Cooperative education: Deepening the concept - Ferreira, Palloma Rosa; Neves de Sousa, Diego (Cooperativismo & Desarrollo, 2019)
Cooperative education is born with the idea of a cooperative. This organization has peculiar characteristics in which cooperation is proposed as an alternative to competition. As one of the pillars of support for cooperative development, it is an explicit need of these organizations. In this attempt, the objective of this work is to carry out a literature review about the concept of cooperative education.
Keywords: Cooperative education; cooperative management; organizational culture